A Potential Role of Bone Morphogenetic Protein 7 in Shell Formation and Growth in the Razor Clam Sinonovacula constricta - Zhao, Jiaxi; Cui, Baoyue; Yao, Hanhan; Lin, Zhihua; Dong, Yinghui (Frontiers in Physiology, 2020)
Bone morphogenetic proteins (BMPs) not only play essential roles in animal bone development but also are associated with embryonic growth, organogenesis cell proliferation and differentiation. To better understand the molecular structure and biological function of BMP7 in Sinonovacula constricta (Sc-BMP7), we cloned and characterized its full-length cDNA sequence in this study. The full length of Sc-BMP7 is 2252bp, including an open reading frame (ORF) of 1257 bp encoding 418 amino acids. The protein sequence included a signal peptide (1–32 aa), a prodomain (38–270 aa) and a TGF-β domain (317–418 aa). The quantitative expression of eleven different tissues in adults showed that Sc-BMP7 was significantly higher expressed in gill, foot and mantle(P<0.05), but lowest in blood and hepatopancreas. In the early development stages, low expression was detected in the stages of unfertilized mature eggs, fertilized eggs, 4-cell embryos, blastula, gastrulae, whereas it increased after trochophore and demonstrated the highest expression in umbo larvae (P<0.01). In shell repair experiment, Sc-BMP7 showed increasing expression level after 12 h. The higher expression of Sc-BMP7 was detected while Ca2+ concentration was reduced in seawater. After inhibiting Sc-BMP7 expression using RNA interference (RNAi) technology, expression of Sc-BMP7 mRNA and protein were significantly down regulated (P < 0.05) in the central zone of mantle (nacre formation related tissue) and the pallial zone of mantle (prismatic layer formation related tissue). Additionally, two SNPs (725G>A, 1115G>A) associated with growth traits was identified in exon of Sc-BMP7 from two groups. These results indicated that Sc-BMP7 might be involved in shell formation and growth.